Climate Change Mitigation Options in the Italian Livestock Sector. (April 2015) - Coderoni, Silvia; Valli, Laura; Canavari, Maurizio
Summary According to official figures, estimated using the UNFCCC methodology, the agricultural sector is responsible for around 10 per cent of EU‐15 greenhouse gas (GHG) emissions. However, these figures rise substantially if we consider the lifecycle of a product, from the cradle to the farm gate. This study investigates six livestock products in Italy, in order to estimate their carbon footprint and to explore their mitigation potential. The products analysed were fresh milk, milk for Parmigiano‐Reggiano cheese, beef, pork, eggs and poultry. Their carbon footprint was estimated using a Life Cycle Assessment approach. Although mitigation measures on the supply side are the focus of European agricultural and climate policies, the study shows that the potential of each individual action is quite limited, due to technical constraints. Nevertheless, some mitigation options can also reduce production costs, generating a win–win situation between public and private benefits. Dissemination programmes, which will be examined in 2015, are important to raise awareness among farmers about climate change scenarios in the agricultural sector and to build capacity for cost‐saving mitigation options. The demand side is also being explored in 2015 to evaluate the mitigation potential, through experimental auctions, of consumer willingness to pay for livestock products with a carbon footprint label.